Investigation of students’ experiences of gendered cultures in engineering workplaces - Male, S.; Gardner, A.; Figueroa, E.; Bennett, Dawn (Taylor & Francis, 2018)
Women remain severely under-represented in engineering in Australia as in all Western countries. This limits the pool of talent, standpoints and approaches within the profession. Furthermore, this under-representation equates to restriction of the benefits of being an engineer mainly to men. Gendered workplace experiences have been found to contribute to women leaving the profession. In this study we explore students’ experiences of gendered cultures in engineering workplaces, using interviews with a purposive sample of 13 students (4 male) recruited following a previous survey. Although the overall experience of workplace learning is positive for many students, male and female engineering students reported experiences consistent with masculine cultures. Educators and employers must proactively lead improvements to the culture in engineering workplaces, prepare students for gendered workplaces and support students to reflect during and after workplace experiences. The experiences presented here could be adapted to enhance inclusivity training.